BRUCELLOSIS: GENERAL DESCRIPTION, ETIOLOGY, EPIDEMIOLOGY, PREVENTION, AND EPIDEMIC CONTROL MEASURES (Лучшие интеллектуальные исследования, 2025)
Abstract: Brucellosis is a widespread, highly dangerous zoonotic infectious disease of polyetiological origin. It is characterized by various routes of transmission, damage to multiple organs and systems—primarily the musculoskeletal and nervous systems—as well as manifestations of intoxication and allergic reactions. The infectious process typically progresses chronically and often leads to disability in affected individuals. This article provides a comprehensive overview of brucellosis, including its etiology, epidemiology, diagnostic and treatment methods, and proposes improvements in prevention and epidemic control strategies. The article also analyzes global experiences and modern approaches aimed at reducing the spread of infectious diseases.